ARTIKULASI-AGREGASI ASPIRASI DALAM PENYUSUNAN APBDES DI DESA TELUK KABUPATEN BATANGHARI JAMBI - Alva Beriansyah; Mariatul Qibtiyah; Novianti Novianti; Navarin Karim (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This article analyzes how village governance articulates and aggregates community aspirations in the preparation of the Village Revenue and Expenditure Budget (APBDes) in Teluk Village, Batanghari Regency. Building on common challenges in village budgeting, the study highlights weak traceability from proposals to budget decisions and limited feedback to citizens, despite the routine implementation of deliberative forums. The research employs a descriptive qualitative approach; data were collected through in-depth interviews, limited observation, and a review of village planning and budgeting documents. The findings show that aspiration articulation operates through multiple channels (social arenas, direct access/WhatsApp, monthly BPD meetings, and proposal-based deliberations). Aspiration aggregation proceeds in stages, beginning with the Village Deliberation (Musyawarah Desa) as an initial consolidation forum, followed by the BPD-led Village Development Planning Meeting (Musrenbangdes) as the arena for reviewing and revising the draft Village Government Work Plan (RKPDes) before it is translated into the APBDes. The aggregation process is shaped by budget ceilings, program feasibility, the readiness of facilities and infrastructure, and alignment with the Village Medium-Term Development Plan (RPJMDes). The article proposes operational instruments in the form of a cross-channel aspiration register and a 4K aggregation metric (RPJMDes alignment, feasibility, readiness, and budget availability) to strengthen decision trails and accountability in village budgeting.